Ileocaecal valve syndrome after surgery in adult patients: myth or reality?. (2nd August 2017) - Palmisano, S.; Silvestri, M.; Troian, M.; Germani, P.; Giudici, F.; de Manzini, N.
Abstract: Aim: The onset of symptoms after removal of the ileocaecal valve (ICV) may be perceived as an unwanted effect of surgery and induce patients to bring unnecessary litigation against surgeons. The aim of our study is to assess the real impact on the quality of life of patients whose ICV has been surgically removed, using three validated questionnaires. Method: In patients who had their ICV removed surgically, the Gastrointestinal Quality of life (GIQLI) questionnaire and those used by the European Organization for research and Treatment of Cancer (EORTC) were administered before and after surgery. The empirical rule effect size method was used to evaluate the clinical significance of the statistical data. Results: We interviewed 225 patients. Data collected through the three questionnaires highlighted a trend towards postoperative improvement of the selected gastrointestinal symptoms compared with the baseline. The GIQLI questionnaire showed a statistically significant improvement in 'pain', 'nausea' and 'constipation' during the follow‐up. Constipation appeared more frequently in patients older than 70 years compared with younger ones. The EORTC‐QLQ‐C30 questionnaire showed a significant correlation between diarrhoea and extended right colectomy at 3 months after surgery, which was not confirmed at 6 months. The EORTC QLQ‐CR29 questionnaire showed a slight deterioration of 'leakage of stools from the anal opening' at 6 months after surgery, but this symptom was not deemed clinically significant. Conclusion: We found that bowel functions in most patients after surgical removal of the ICV were satisfactory. Providing patients with a comprehensive and exhaustive informed consent during preoperative consultations could promote patient trust and avoid misunderstandings.